2009
DOI: 10.1038/nrd2907
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle kinases as therapeutic targets for cancer

Abstract: Several families of protein kinases orchestrate the complex events that drive the cell cycle, and their activity is frequently deregulated in hyperproliferative cancer cells. Although several molecules that inhibit cell cycle kinases have been developed and clinically screened as potential anticancer agents, none of these has been approved for commercial use and an effective strategy to specifically control malignant cell proliferation has yet to be established. However, recent genetic and biochemical studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
665
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 809 publications
(680 citation statements)
references
References 156 publications
11
665
0
4
Order By: Relevance
“…Previous studies revealed that cyclin D1-overexpressing cells demonstrate constitutive CDK activity and increased sensitivity to CDK4/6 inhibitors (30,31). Cyclin D1 was also demonstrated to be implicated in resistance to inhibitors of ERBB2, EGFR, and ER signaling (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that cyclin D1-overexpressing cells demonstrate constitutive CDK activity and increased sensitivity to CDK4/6 inhibitors (30,31). Cyclin D1 was also demonstrated to be implicated in resistance to inhibitors of ERBB2, EGFR, and ER signaling (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…To measure the time resolved gene responses to Roc-A, RNA was isolated from Roc-A-treated (50 nM) normal T and Jurkat T cells at t 5 [0, 1,2,3,4,6,8,10,14,20,28,36] and t 5 [0. 5,1,2,3,4,5,6,7,8,10,12,14,16,20,24,28,32,36] hr, respectively. The quality of total RNA was controlled with an Agilent 2100 Bioanalyzer (Agilent Technologies GmbH, Berlin, Germany).…”
Section: Rna Preparation and Dna Microarray Analysismentioning
confidence: 99%
“…[1][2][3] Therefore, targeting the cancer cell cycle machinery has been considered to be a rational strategy for cancer treatment. 4 Cell division is governed by cyclin dependent kinases (CDKs) that are tightly regulated by cyclins and CDK inhibitors (CDKIs). Tumor-associated cell cycle defects often show alterations in CDK expression or/and activity.…”
mentioning
confidence: 99%
“…Pharmacological interventions that selectively inhibit checkpoint-mediated cell cycle arrest in cancer cells, but not in normal cells, could be exploited to increase cancer kill. 2 The S/G 2 checkpoints have recently been targeted to achieve this goal. 2 Since many cancer cells have a defective G 1 checkpoint (e.g., due to mutations in the tumor suppressor genes, including p53, p21, and Rb), they rely on an intact S/G 2 checkpoint to repair damaged DNA.…”
Section: Introductionmentioning
confidence: 99%
“…2 The S/G 2 checkpoints have recently been targeted to achieve this goal. 2 Since many cancer cells have a defective G 1 checkpoint (e.g., due to mutations in the tumor suppressor genes, including p53, p21, and Rb), they rely on an intact S/G 2 checkpoint to repair damaged DNA. Inhibition of the S/G 2 checkpoints would cause these G 1 checkpoint-defective cancer cells to undergo mitotic catastrophe and eventually cell death, while normal cells remain arrested in the G 1 phase for DNA repair.…”
Section: Introductionmentioning
confidence: 99%